Mapping the intellectual structure of green economy and sustainability: a bibliometric analysis of global research trends and policies - Ali Imtiaz; Chi Yuanying; Muhammad Farukh Shahzad; Abdul Raheel; Fahad Sabah; Raheem Sarwar (Cogent Economics & Finance)
The green economy has emerged as a pivotal framework for reconciling economic growth with sustainability, yet its global research landscape remains fragmented and under explored. This study addresses this gap through a comprehensive bibliometric analysis of 1,471 Scopus-indexed publications (2007–2024), employing VOSviewer and Python to map research trends, collaborations, and thematic clusters. The primary contributions of this work are threefold: First, it systematically quantifies global research disparities, revealing China’s dominance (38.8% of publications) and the under representation of developing nations. Second, it identifies interdisciplinary thematic clusters; renewable energy transitions, policy governance, and economic decarbonization; while exposing critical gaps in addressing social equity and localized strategies for low-income regions. Third, it proposes actionable policy pathways, including North-South research partnerships and digital technology integration such as, AI-driven governance, blockchain for transparency, to bridge these gaps. Findings highlight exponential growth in research post-2016, driven by global climate agreements, but emphasize persistent imbalances in geographic and thematic focus. By advocating for inclusive, interdisciplinary approaches, this study provides a road map for aligning green economy strategies with the United Nations Sustainable Development Goals (SDGs). The results underscore the urgency of prioritizing social equity alongside technological innovation to ensure sustainable global transitions.